PSYCHOLOGICAL SIGNIFICANCE OF PRACTICAL EXERCISE IN FORMING STUDENTS' TECHNICAL THINKING. (Universal International Scientific Journal, 2026)
This article discusses the role, importance and didactic possibilities of construction activities in the process of developing technical thinking in students. It is scientifically proven that construction activities serve to form logical thinking, problem solving, analysis and independent decision-making skills in students. The article analyzes the pedagogical advantages of working with various types of constructors (paper-plastic, wooden, LEGO, magnetic constructors, etc.), their effectiveness in stimulating technical creativity. It also shows ways to integrate construction activities with the modern STEAM approach, project activities and problem-based learning. The results of the study confirm that construction activities are an important component of technological education in the formation of technical thinking and practical competencies in students.
Keywords: technical thinking; design training; technical creativity